Body satisfaction and Depression Symptoms among Children with Precocious Puberty in Baghdad City - hussein, adraa; Ma`ala, Eqbal (Iraqi National Journal of Nursing Specialties, 2019)
Objective: to evaluate body image and depression symptoms of children with precocious puberty, and find out association between children`s sociodemographic characteristics and their body image and depression signs. Methodology: A cross sectional study, sample of (80) child from both gender, > 7 years were included due to their ability to express their own feeling, diagnosed with precocious puberty, attending out-patient endocrine clinics at pediatric hospitals in Baghdad city. Data collected, during the period from May to November 2018. Consent form has taken from children and their guardians to participate in study. Child body image scale (CBIS) was used to evaluate children body satisfaction (1) and Mood and feeling questionnaire (M&FQ) to evaluate children degree of depression symptoms (2), the approved has taken from the ownership directly. SPSS version 23 was used to analyze data by applying descriptive analysis (percentages, frequencies and mean) as well as inferential analysis (T-test). Results: the finding shows that most children with precocious puberty experience body dissatisfaction, more than half of children experience depression signs, school achievement shows significant association with their depression signs. Recommendation: the study recommend to emphasis on psychosocial assessment during routine physical examination, in addition to provide psychological support for those children especially girls